A checklist of the bats of Peninsular Malaysia and progress towards a DNA barcode reference library - Lim, V.C.; Ramli, R.; Bhassu, S.; Wilson, J.J. (Public Library of Science, 2017)
Several published checklists of bat species have covered Peninsular Malaysia as part of a broader region and/or in combination with other mammal groups. Other researchers have produced comprehensive checklists for specific localities within the peninsula. To our knowledge, a comprehensive checklist of bats specifically for the entire geopolitical region of Peninsular Malaysia has never been published, yet knowing which species are present in Peninsular Malaysia and their distributions across the region are crucial in developing suitable conservation plans. Our literature search revealed that 110 bat species have been documented in Peninsular Malaysia; 105 species have precise locality records while five species lack recent and/ or precise locality records. We retrieved 18 species from records dated before the year 2000 and seven species have only ever been recorded once. Our search of Barcode of Life Datasystems (BOLD) found that 86 (of the 110) species have public records of which 48 species have public DNA barcodes available from bats sampled in Peninsular Malaysia. Based on Neighbour-Joining tree analyses and the allocation of DNA barcodes to Barcode Index Number system (BINs) by BOLD, several DNA barcodes recorded under the same species name are likely to represent distinct taxa. We discuss these cases in detail and highlight the importance of further surveys to determine the occurences and resolve the taxonomy of particular bat species in Peninsular Malaysia, with implications for conservation priorities.